Pengaruh Prestasi Kerja Dan Pengalaman Kerja Terhadap Promosi Jabatan - Medhiantari, Ida Ayu Nithya; Yuniari, Made (E-Jurnal Manajemen, 2014)
Job promotion is an employee transferred from one job to another greater responsibility and his level was higher. The purpose of this study was to determine the effect of job performance and work experience of employees on promotion either simultaneously or partial. This study took place at PT. Bank Rakyat Indonesia (Persero) Tbk. Gajah Mada, Denpasar branch located in Gajah Mada street no 5-7. Data collected by distributing questionnaires to a number of bank. Engineering analysis using multiple regression analysis. Based on the results of analysis show that the variable job performance and employee experience significant effect simultaneously on promotion at PT. Bank Rakyat Indonesia (Persero) Tbk. Gajah Mada, Denpasar. Variables work performance and work experience of employees also a significant effect partially on promotion at PT. Bank Rakyat Indonesia (Persero) Tbk. Gajah Mada branch Denpasar
Keywords: promotion; job performance; work experience